Untargeted Metabolomics Approach in Halophiles: Understanding the Biodeterioration Process of Building Materials - Adamiak, Justyna; Bonifay, Vincent; Otlewska, Anna; Sunner, Jan A.; Beech, Iwona B.; Stryszewska, Teresa; Kańka, Stanisław; Oracz, Joanna; Żyżelewicz, Dorota; Gutarowska, Beata (Frontiers in Microbiology, 2017)
The aim of the study was to explore the halophile metabolome in building materials using untargeted metabolomics which allows for broad metabolome coverage. For this reason, we used high-performance liquid chromatography interfaced to high-resolution mass spectrometry (HPLC/HRMS). As an alternative to standard microscopy techniques, we introduced pioneering Coherent Anti-stokes Raman Scattering Microscopy (CARS) to noninvasively visualize microbial cells. Brick samples saturated with salt solution (KCl, NaCl (two salinity levels), MgSO4, Mg(NO3)2), were inoculated with the mixture of preselected halophilic microorganisms, i.e. bacteria: Halobacillus styriensis, H. naozhouensis, H. hunanensis, Staphylococcus succinus, Marinococcus halophilus, Virgibacillus halodenitryficans and yeast: Sterigmatomyces halophilus and stored at 28 °C and 80 % relative humidity for a year. Metabolites were extracted directly from the brick samples and measured via HPLC/HRMS in both positive and negative ion modes. Overall, untargeted metabolomics allowed for discovering the interactions of halophilic microorganisms with buildings materials which together with CARS microscopy enabled us to elucidate the biodeterioration process caused by halophiles. We observed that halophile metabolome was differently affected by different salt solutions. Furthermore, we found indications for haloadaptive strategies and degradation of brick samples due to microbial pigment production as a salt stress response. Finally, we detected changes in lipid content related to changes in the structure of phospholipid bilayers and membrane fluidity.